Factors Affecting the Adoption of Forage Technologies in Smallholder Dairy Production Systems in Lushoto, Tanzania - Ndah, Hycenth T.; Schuler, Johannes; Nkwain, Vandoline N.; Nzogela, Beatus; Mangesho, Walter E.; Mollel, Richard; Loina, Rose; Paul, Birthe K. (International Center for Tropical Agriculture, 2017)
Despite population pressure and the urgent need for dairy production to be doubled by 2050, there is still a significant deficit in milk production in sub-Saharan Africa (SSA). Lack of quantity and quality feed is one of the major factors causing unsatisfactory milk yields. This Working Paper assessed the adoption potential of forage technologies in Lushoto, Tanga district, Tanzania. We carried out an extensive literature review of past work on smallholder dairy production in SSA and Tanzania, and the adoption rate of forage technologies; visited and observed farmers’ fields in Lushoto; carried out interviews with farmers; and used a Qualitative participatory expert-based Assessment Tool for Forage Technology adoption (QATo-FT) in a multi-stakeholder workshop. Results showed that the adoption rate of improved forage technologies in Lushoto is still in the early stages following classical diffusion theories. The farmers’ interviews revealed that while the triggering factors for adoption were related to the shortage of feed and soil conservation problems, the potential economic advantages were not as dominant as expected. Farmers reported the reasons for sustaining the practices of growing improved forages as the year-round availability of fodder, increased fodder demand and accumulated benefits. The low actual adoption rates contrasted with results from the QATo-FT assessment that revealed a high overall adoption potential for Lushoto. The following factors all exerted a positive influence on adoption potential: the general receptive nature of the community towards the technology; the expectations of improved forages on ecological benefits; and the role of promoting institutions. Factors exerting a weaker influence included the political and institutional framework at regional level, and products and input markets conditions for forage and overall livestock farming. Most important barriers to adoption were related to the whole farming system and the wider environment. The opportunity cost for labor was low due to lack of off-farm income possibilities, hence making it favorable for farmers to collect fodder from distant places instead of saving labor through growing forages closer to the homestead. Further, several other livestock management factors confounded potential gains in milk production through improved forages: current breeds were often not sufficiently high yielding to respond to improved feeding; providing water to zero grazing animals was not always achievable for labor-constrained farms; many farmers let forages overgrow for use in times of scarcity (dry season) which led to lower-than-necessary forage being fed to animals; sufficient planting material and extension advice on forage management and harvesting was not always available; milk prices were low and would not be increased if the volume of milk production did not increase (the collection center was operating at < 50% capacity). To increase future forage adoption rates, it is recommended to invest in knowledge transfer, more effective local authority and extension structures, stronger multi-stakeholder partnerships, access to loan and credit facilities, improvement of off-farm income possibilities, better access to input markets including AI and forage planting material, and more favorable output markets. By doing this, the performance of existing heads of cattle for the region would be improved, milk yields would increase and eventually farmers’ income levels would be enhanced. This could improve nutrition, and eventually contribute to poverty alleviation in SSA.